Lysosomal cathepsins act in concert with Gasdermin-D during NAIP/NLRC4-dependent IL-1β secretion - Laura Migliari Branco; Marcelo Pires Amaral; Henning Boekhoff; Ana Beatriz Figueiredo de Lima; Ingrid Sancho Farias; Silvia Lucena Lage; Gustavo José Silva Pereira; Bernardo Simões Franklin; Karina Ramalho Bortoluci (Cell Death and Disease, 2022)
Abstract The NAIP/NLRC4 inflammasome is classically associated with the detection of bacterial invasion to the cytosol. However, recent studies have demonstrated that NAIP/NLRC4 is also activated in non-bacterial infections, and in sterile inflammation. Moreover, in addition to the well-established model for the detection of bacterial proteins by NAIP proteins, the participation of other cytosolic pathways in the regulation of NAIP/NLRC4-mediated responses has been reported in distinct contexts. Using pharmacological inhibition and genetic deletion, we demonstrate here that cathepsins, well known for their involvement in NLRP3 activation, also regulate NAIP/NLRC4 responses to cytosolic flagellin in murine and human macrophages. In contrast to that observed for NLRP3 agonists, cathepsins inhibition did not reduce ASC speck formation or caspase-1 maturation in response to flagellin, ruling out their participation in the effector phase of NAIP/NLRC4 activation. Moreover, cathepsins had no impact on NF-κB-mediated priming of pro-IL-1β, thus suggesting these proteases act downstream of the NAIP/NLRC4 inflammasome activation. IL-1β levels secreted in response to flagellin were reduced in the absence of either cathepsins or Gasdermin-D (GSDMD), a molecule involved in the induction of pyroptosis and cytokines release. Notably, IL-1β secretion was abrogated in the absence of both GSDMD and cathepsins, demonstrating their non-redundant roles for the optimal IL-1β release in response to cytosolic flagellin. Given the central role of NAIP/NLRC4 inflammasomes in controlling infection and, also, induction of inflammatory pathologies, many efforts have been made to uncover novel molecules involved in their regulation. Thus, our findings bring together a relevant contribution by describing the role of cathepsins as players in the NAIP/NLRC4-mediated responses.